Insurance product against rainfall for horticultural producers (Uruguay State Insurance Bank) still operational 6 years after an IFPRI-led pilot - CGIAR Research Program on Policies, Institutions, and Markets (2021)
Following an IFPRI-led pilot, this government-sponsored insurance program is in use since 2015 and sold as an add-on to an older and more established hail insurance product.